Macroeconomic, Corporate Fundamentals, Systematic Risk on Firm Value: Evidence from Indonesian Manufacturing Sector - Mappadang, Agoestina (University of Merdeka Malang, 2021)
This paper aims to study the connection between the effect of macroeconomics, corporate fundamentals on systematic risk, and the firm’s value of the Indonesian manufacturing industry listed on the Indonesian Stock Exchange period 2015-2020. A total of 522 object analyses in this study with the purposive sampling method. This paper found that the direction and magnitude of the impact of firm value depend on macroeconomic measurement variables: interest rates, exchange rates, and the company’s fundamental measurement variables: leverage and capital expenditure. The paper also found that the macroeconomic positively affects firm value, and leverage has a significant positive effect on firm value. At the same time, capital expenditure shows different results in response to the firm value, that is, negatively significant. In particular, a systematic risk as a mediating variable becomes a significant and positive driver of macroeconomics and leverage on firm value. However, different results indicate that capital expenditure negatively affects the firm value if mediated by the systematic risk. The implication of this research is beneficial to enable companies and investors to make the right analytical decision in the Indonesian capital market in this pandemic covid-19 situation.JEL: E43, G10, G32